2016
DOI: 10.1007/s00170-016-9850-3
|View full text |Cite
|
Sign up to set email alerts
|

Hole-making processes and their impacts on the microstructure and fatigue response of aircraft alloys

Abstract: A comparative study on conventional drilling and helical milling has been reported under the context of aircraft alloy hole making. The impacts of these two different machining processes on the microstructures and the fatigue performance of different aircraft alloys have been elaborated. Results show that both alloys undergo more severe surface/subsurface plastic deformation under conventional drilling comparing to helical milling process. Helical milling leads to a longer coupon fatigue life compared to conve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
35
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(41 citation statements)
references
References 34 publications
(38 reference statements)
2
35
0
Order By: Relevance
“…Surface roughness is mostly used as an index to determine the surface finish and, consequently, workpiece quality in machining processes [67][68]. Besides, it is an important requirement to evaluate machined surfaces, affecting lubrication, friction, corrosion resistance, fatigue resistance, and other mechanical properties [69][70][71]. The average surface roughness, Ra, and the average maximum height of the profile, Rz, were evaluated in the borehole surfaces of AISI H13 hardened steel obtained through helical milling.…”
Section: Roughness On Helical Milling Of Aisi H13 Hardened Steelmentioning
confidence: 99%
“…Surface roughness is mostly used as an index to determine the surface finish and, consequently, workpiece quality in machining processes [67][68]. Besides, it is an important requirement to evaluate machined surfaces, affecting lubrication, friction, corrosion resistance, fatigue resistance, and other mechanical properties [69][70][71]. The average surface roughness, Ra, and the average maximum height of the profile, Rz, were evaluated in the borehole surfaces of AISI H13 hardened steel obtained through helical milling.…”
Section: Roughness On Helical Milling Of Aisi H13 Hardened Steelmentioning
confidence: 99%
“…This is because aircrafts constantly operate under vibration/shock conditions where thousands of fastener holes in the fuselage skins are prone to fatigue [2]. Fatigue cracks normally initiate and propagate after the fastened holes create regions of concentrated stress; therefore, the reliability of aircraft structures depends on their fatigue life, which is directly related to hole quality [3]. In addition, the drilling process is normally amongst the last steps of final assembly of fabricating parts, where poor hole quality might lead to part rejection, which can become costly if optimum process parameters, tools, or drilling operations are not taken into consideration [4].…”
Section: Introductionmentioning
confidence: 99%
“…Using design of experiment methods, such as Taguchi and response surface, showed that feed rate and cutting speed are the most influential parameters on the drilling of steels. Different machining methods, such as ultrasonic drilling, and tool selection leads to better surface quality and drilling of soft materials, such as Al, and helical milling increases fatigue life [ 18 , 19 , 20 ]. The effect of pre-hole drilling on Al 6061-7075 with uncoated HSS drills showed that pre-holes reduce cutting force and improve surface roughness and chip generation [ 21 ].…”
Section: Introductionmentioning
confidence: 99%